The Efficacy of Integrative Medicine in Managing Chronic Pain - Rajia, Rajia (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the effectiveness of integrative medicine in managing chronic pain, investigating various complementary therapies, including acupuncture and mindfulness-based stress reduction. Research Design and Methodology: This study employed a mixed-methods approach, conducting a systematic review of existing literature and analyzing quantitative data to assess the impact of integrative interventions on chronic pain outcomes. Findings and Discussion: The research findings suggest that integrative medicine modalities, including acupuncture and mindfulness-based interventions, demonstrate promising results in reducing pain intensity, improving physical function, and enhancing overall well-being among individuals with chronic pain. However, limitations such as small sample sizes and short-term follow-up periods underscore the need for further research to validate these findings and explore long-term efficacy. Implications: These findings have a significant impact on scientific knowledge and clinical practice in the management of chronic pain. Integrative medicine offers a holistic and patient-centered approach that complements conventional treatments, highlighting the potential to address the multifaceted nature of chronic pain and improve patient's quality of life. Future research should focus on overcoming methodological limitations and integrating integrative approaches into mainstream healthcare to optimize patient care.